The fate of the dead : studies on the Jewish and Christian apocalypses - Bauckham, Richard. (Novum Testamentum, Supplements, 1998)
These studies focus on personal eschatology in the Jewish and early Christian apocalypses. The apocalyptic tradition from its Jewish origins until the early middle ages is studied as a continuous literary tradition, in which both continuity of motifs and important changes in understanding of life after death can be charted. As well as better known apocalypses, major and often pioneering attention is given to those neglected apocalypses which portray human destiny after death in detail, such as the Apocalypse of Peter, the Apocalypse of the Seven Heavens, the later apocalypses of Ezra, and the four apocalypses of the Virgin Mary. Relationships with Greco-Roman eschatology are explored. Several chapters show how specific New Testament texts are illuminated by close knowledge of this tradition of ideas and images of the hereafter.